Validation of the Elementary Social Behavior Assessment: A Measure of Student Prosocial School Behaviors. (June 2015) - Pennefather, Jordan T.; Smolkowski, Keith
We describe the psychometric evaluation of the Elementary Social Behavior Assessment (ESBA™), a 12-item scale measuring teacher-preferred, positive social skills. The ESBA was developed for use in elementary school classrooms to measure teacher perceptions of students using time-efficient, web-based data collection methods that allow quick and reliable universal screening. Results from two studies demonstrate that the ESBA has robust internal consistency, a single-dimension, and strong criterion validity. The ESBA seems suited for use within multi-tiered models that address classroom social behavior within early elementary classrooms. It enables teachers to efficiently identify and support students who need additional help learning how to ask for help, complete seatwork, get along with peers, and acquire the other skills that allow them to become successful students.